Enkripsi End-to-End pada Aplikasi WhatsApp Menggunakan Metode AES-256 - Totnay, Euis Clarita Tiara Tunas; Seran, Maria Marsela; Tusala, Vallient Vandem Yaved; Mau, Silverius Triyanto; To, Hermina Loka (Blantika: Multidisciplinary Journal, 2025)
The rapid advancement of digital communication demands reliable data protection systems to safeguard privacy and information security. WhatsApp, as the most widely used instant messaging application, has implemented an End-to-End Encryption (E2EE) system using AES-256 and ECDH Curve25519 algorithms within the Signal Protocol. This study aims to analyze the security architecture of WhatsApp’s E2EE and evaluate its effectiveness and limitations in addressing modern cybersecurity threats. A descriptive qualitative approach was employed through a literature study, examining technical documentation, scientific journals, and limited encryption-decryption simulations. The analysis reveals that WhatsApp successfully integrates symmetric and asymmetric cryptography through a key exchange mechanism (Identity Key, Signed Pre Key, One-Time Pre Key) and the Double Ratchet Algorithm, which generates unique session keys for each message. This system ensures confidentiality, integrity, and forward secrecy, meaning that no third party; including WhatsApp servers—can read the message contents. However, vulnerabilities still exist in endpoint security, metadata management, and backup systems that are not fully protected by E2EE. In conclusion, WhatsApp’s E2EE system is a robust and adaptive model for secure digital communication, though it still requires reinforcement in user-end protection and data management policies. This research is expected to serve as a reference for developing more secure, transparent, and equitable communication systems in the digital age.